Transition to Adult Mental Health Services for Young People With ADHD. Issue 6 (April 2018) - Reale, Laura; Costantino, Maria Antonella; Sequi, Marco; Bonati, Maurizio
Objective: To investigate the care management and continuity from child to adult mental health service for young adults with ADHD.Method: A questionnaire survey from 18 Regional ADHD Pediatric Centers (RAPC) in Lombardy, Italy, was used to collect data on transition protocols and population served, and to track the pathway of care of ADHD patients once they reached adulthood.Results: Twenty-eight percent of RAPC had transition protocols and 3% of the population annually served were potential referrals to adult service. Of 52 patients who turned 18 years, just over 70% were monitored by the general practitioner, of those 5 with RAPC support. One fifth of patients continued to use mental health services, the majority was still monitored by the RAPC, and only three by services for adult.Conclusion: Managing the process of transition to adult services in mental health care remains a need to be prioritized and better defined for ADHD patients.